Chapter 1 Stigmatization as a Tool of Cultural Violence - Burke, Danita Catherine (Taylor & Francis, 2023)
Chapter 1 presents the argument that at the heart of hardline anti-sealing activism is a strategy of stigmatization to both dissuade individuals, business and countries from association with anyone or anything connected to the practice of sealing and to justify and normalize of activist behaviours, actions and attitudes against predominately working class rural and coastal peoples. To unpack the relationship between cultural violence, stigmatization and activism, the chapter introduces the concept of culture. By introducing the meaning of culture the chapter helps to set the stage for the examination in the book on the implications of breaking down the meanings and practices of a group through stigmatizing and alienating them. The chapter goes on to illustrate how the stigmatization of a peoples' culture can lead to the possible destruction of a group's cohesion by making group members fearful of, and threatened against, openly expressing or participating in the activities and beliefs that are central to the fabric of the group's identity.